Techno-Economic Analysis of Integrated Solar-Wind System for EV Charging Station - Juana, Eki; Hiron, Nurul; Faridah, Linda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to comprehensively evaluate the potential, technical, and economic feasibility of implementing a hybrid solar-wind power generation system as a sustainable energy solution to support the operation of Electric Vehicle Charging Stations (EVCS) in Pangandaran Regency, Indonesia. Through simulations using HOMER Energy software, this research analyzes the renewable energy resource potential in the region, with an average solar radiation of 5.03 kWh/m² and an annual wind speed of 5.03 m/s. The simulation results show that the optimal system configuration consists of 335 solar panels (113.9 kWp) and 6 wind turbines (9 kW), capable of generating 177,791 kWh of annual electricity, which is sufficient to meet the energy needs of the EVCS with a reasonable margin. The economic analysis conducted indicates that although there is a significant initial investment cost, the hybrid system has a Net Present Cost (NPC) of IDR 5,825,862,785 with a Cost of Energy (COE) of IDR 2,245/kWh, demonstrating that this investment offers long-term economic benefits. Furthermore, the sensitivity study performed shows that the system is relatively robust to changes in environmental conditions and other system parameters. The results of this research provide strong evidence that the hybrid solar-wind power generation system is technically, economically, and environmentally viable for supporting the development of electric vehicle charging infrastructure in areas with high renewable resource potential, such as Pangandaran. The implementation of this system is expected to reduce dependence on fossil fuels, lower greenhouse gas emissions, and promote the transition towards clean and sustainable energy in Indonesia